Effects of Mycorrhizal on The Growth and Yield of Cayenne Pepper (Capsicum frutescens L.) - Sumiyati Tuhuteru; Rein Edward Yohanes Rumbiak; Inrianti Inrianti (Institut Pertanian Bogor, 2024)
Innovations are required to increase the production of cayenne pepper (Capsicum frutescens L), mainly due to the need for more quality land, such as dry land in Wamena. The innovation uses biological microorganisms that positively impact plants, such as arbuscular mycorrhizal fungi (AMF). Therefore, this experiment aimed to determine the response of the growth and yield of cayenne pepper plants cultivated in dry land to the application of mycorrhiza. The research was conducted using a completely randomized design with one factor: the mycorrhizae dose (0, 20, 50, 80, and 120 g). The research results were analyzed using ANOVA, and the analysis process continued with the 5% level DMRT test. The research results on the growth of cayenne pepper are visible in the plant height parameters of the 80 g treatment (75 DAP: 93.4 cm) and the 120 g treatment (95 DAP: 103.3 cm). Then, the stem diameter parameter showed a real influence by the 120 g mycorrhiza treatment at 35 and 75 DAP and the 80 g mycorrhiza treatment at 95 DAP. The excellent response of plants to the 80 g and 120 g mycorrhiza treatments also impacted the plant's total chlorophyll content and the number of leaves produced, which then impacted the number of productive branches. So, the effect on the yield of cayenne pepper plants is that the number of fruits treated with 80 g of mycorrhiza was 89.7 fruits, with the weight of the heaviest cayenne pepper fruit being 68.0 g by the treatment of 120 g of mycorrhiza with a fresh weight of 17.6 g and a total dry plant of 10.2 g compared to the control. Keywords: Arbuscular mycorrhiza, Biofertilizers, fungi, marginal land, Wamena